Two factor reprogramming of human neural stem cells into pluripotency. - Mark E Hester; Sungwon Song; Carlos J Miranda; Amy Eagle; Phillip H Schwartz; Brian K Kaspar (PLoS ONE)
Background Reprogramming human somatic cells to pluripotency represents a valuable resource for the development of in vitro based models for human disease and holds tremendous potential for deriving patient-specific pluripotent stem cells. Recently, mouse neural stem cells (NSCs) have been shown capable of reprogramming into a pluripotent state by forced expression of Oct3/4 and Klf4; however it has been unknown whether this same strategy could apply to human NSCs, which would result in more relevant pluripotent stem cells for modeling human disease. Methodology and principal findings Here, we show that OCT3/4 and KLF4 are indeed sufficient to induce pluripotency from human NSCs within a two week time frame and are molecularly indistinguishable from human ES cells. Furthermore, human NSC-derived pluripotent stem cells can differentiate into all three germ lineages both in vitro and in vivo. Conclusions/significance We propose that human NSCs represent an attractive source of cells for producing human iPS cells since they only require two factors, obviating the need for c-MYC, for induction into pluripotency. Thus, in vitro human disease models could be generated from iPS cells derived from human NSCs.